Perspektif Islam dan Kristen Terhadap Multikulturalisme - Zaiddin, Zaiddin (Al-Adyan: Journal of Religious Studies, 2020)
The relationship between Islam and Christianity often appears in a paradoxical face.  In the aspects of power and politics there are often tensions, conflicts and even violence.  However, in the aspects of socio-cultural, tolerance, mutual respect and cooperation still appear to be running, as if two religions promote multiculturalism.  This research discusses how multiculturalism is in the perspective of Islam and Christianity.  This article is compiled using the multiculturalism approach itself by referring to books and articles discussing about issues of multiculturalism about the two religions.  The results of the research conclude that normatively Islam does not only recognize the existence of religions but also respects and gives freedom to their adherents to practice their beliefs as well as cultural diversity.  Meanwhile, in both the Old and New Testaments, Jesus also made a similar movement.  Even as a continuation of the teachings of Judaism, he came not to destroy it, but to fulfill and perfect it.  Jesus also respected the different sects and understandings of each religious group.Relasi Islam dan Kristen seringkali tampil dalam wajah paradok. Pada aspek-aspek kekuasan dan politik sering diwarnai ketegangan, konflik bahkan kekerasan. Namun pada aspek-aspek sosial budaya, toleransi, saling menghargai dan kerjasama masih tampak berjalan yang mengandaikan kedua agama meruangkan multikulturalisme. Tulisan ini membahas bagaimana multikulturalisme dalam perspektif Islam dan Kristen. Artikel ini disusun denga menggunakan pendekatan multikulturalisme sendiri dengan merujuk buku-buku dan artikel yang berbicara tentang isu-isu multikulturalisme terhadap kedua agama tersebut. Hasil riset menyimpulkan bahwa secara normatif Islam tidak hanya mengakui keberadaan agama-agama tapi juga menghormati dan memberi kebebasan pada pemeluk-pemeluknya untuk mengamalkan keyakinannya itu termasuk juga keragaman budaya. Sementara baik dalam Perjanjian Lama maupun Perjanjian Baru, Yesus juga melakukan gerakan serupa. Bahkan sebagai pelanjut ajaran agama Yahudi, ia datang bukan untuk menghancurkannya, melainkan untuk menggenapi dan menyempurnakannya. Yesus juga menghormati perbedaan aliran dan pemahaman masing-masing kelompok keagamaan.